2020
DOI: 10.4317/jced.57387
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the stresses produced on the bone implant/tissue interface to the different insertion angulations of the implant - a three-dimensional analysis by the finite elements method

Abstract: Background The present study aimed to assess the stresses produced on the surface of the bone tissue around dental implants with three different insertion angulations subjected to axial and oblique loading. Material and Methods The study was created according to the recommendations of the Checklist for Reporting In-vitro Studies (CRIS). The Straumann™ bone level RC (4.1 x 10 mm) implant, Cone Morse connection (CM), RC Straumann Variobase™ with abutment (3.5 mm) was plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Installing implants in inadequate positions may lead to damages to peri-implant bone tissue. Thus, the literature shows that, in angled models subjected to axial or oblique loads, the stability of the implant/prosthesis system was compromised ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Installing implants in inadequate positions may lead to damages to peri-implant bone tissue. Thus, the literature shows that, in angled models subjected to axial or oblique loads, the stability of the implant/prosthesis system was compromised ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Along with the development of new implant systems, there was an increased need for investigation and research in the field to understand the actual effects of such modernism in the behavior of peri-implant tissues ( 2 , 3 ). Hence, studies assessing bone behavior in the treatment with dental implants have been showing that among the main enemies of peri-implant tissues are the absence of planning and implant placement in sites and positions not recommended by the manufacturers ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported a decrease in stress values in the cortical bone with an increase in the implant length and thickness [31][32][33]. Further, the generated stress was reported to increase with an increase in the front-rear and left-right angles of the implant [34][35][36]. The implant placement location has been divided into anterior, premolar, and posterior teeth, and the magnitude of stress has been reported to decrease in the order of posterior teeth, premolars, and anterior teeth [37].…”
Section: Introductionmentioning
confidence: 89%
“…However, the biomechanical behavior of implants, intermediate abutments, and prosthetic crowns can directly affect prosthesis geometry and placement in the mouth (Tian et al, 2012). Implants at the bone level, angled at 30° under oblique loads, suggested a significant bone loss risk (Brum et al, 2020). That disagrees with one of the primary objectives of dental implant treatments, which includes achieving successful results from functional, esthetic, and phonetic standpoints and high long-term predictability and stability (Buser et al, 2017).…”
Section: Introductionmentioning
confidence: 99%